2010
DOI: 10.1021/jf102017s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environment and Genotype on Phenolic Acids in Wheat in the HEALTHGRAIN Diversity Screen

Abstract: Phenolic acid content and composition have been determined in 26 wheat genotypes grown in Hungary over three consecutive years and at three additional locations (France, United Kingdom, and Poland) during the third year. Fractions comprising free, soluble conjugated, and bound phenolic acids were analyzed using HPLC with measurements being made for individual phenolic acids in each fraction. Statistically significant differences in phenolic acid content occurred across the different growing locations with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
89
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 28 publications
22
89
5
Order By: Relevance
“…Lastly, for the free form Duilio had the highest content (6.7 ± 3.6 mg/ kg dm) and Dylan the lowest (3.1 ± 1.3 mg/kg dm). In agreement with previous data (Fernandez-Orozco et al, 2010;Li et al, 2008;Martini et al, 2014), the free form showed the highest variability (RSD ¼ 56%), followed by the conjugated form (17%) and by the bound form, which showed the lowest variability (RSD ¼ 14%).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Lastly, for the free form Duilio had the highest content (6.7 ± 3.6 mg/ kg dm) and Dylan the lowest (3.1 ± 1.3 mg/kg dm). In agreement with previous data (Fernandez-Orozco et al, 2010;Li et al, 2008;Martini et al, 2014), the free form showed the highest variability (RSD ¼ 56%), followed by the conjugated form (17%) and by the bound form, which showed the lowest variability (RSD ¼ 14%).…”
Section: Resultssupporting
confidence: 93%
“…growing temperature and rainfall from anthesis to maturity). More recently, a study within the HEALTHGRAIN Project reported that environment affects PA content (especially the free and conjugated forms) in common wheat, observing that rainfall level before heading period may be a more relevant factor than total precipitation (Fernandez-Orozco et al, 2010). Regarding specifically durum wheat, Menga et al (2010) observed that TPC was mainly influenced by the growing area and secondly by genotype and growing area  genotype interaction.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Statistically significant year-to-year differences -higher FFA amounts in 2009 in comparison with 2010 in emmer and spring wheat species (Figure 2) -may be affected by lower sum of precipitation and higher average temperatures in 2009 (Table 1). Shewry et al (2010) reported for free phenolic acids r = 0.899, P = 0.015 for average temperature and r = -0.706, P = 0.0117 for precipitation heading to harvest. The respective data for conjugated phenolic acids were r = 0.753, P = 0.084 for average temperature and r = -0.744, P = 0.090 for precipitation heading to harvest.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activity of wheat and its different fractions usually depends on the variety examined (Yu et al 2002a,b), and the location where it is grown . Environmental factors (such as temperature stress, solar radiation and irrigation), and the interactions between environmental factors and genotype can modulate the antioxidant activity of wheat (Moore et al 2006, FernandezOrozco et al 2010, Shewry et al 2010.…”
mentioning
confidence: 99%